Effect of probiotic supplementation on the performance of White Pekin Ducks - Shibi Thomas K (Department of Poultry Science, College of Veterinary and Animal Sciences, 2003)
One hundred and forty-four straight run day-old broiler ducklings, randomly divided into three treatment groups of four replicates with 12 ducklings each were used to study the effect of probiotic 'Livesac' (Lactic acid bacilli, live yeast cells and traces of enzymes) supplementation on the performance of Vigova variety of White Pekin ducks for a period of eight weeks. Standard broiler rations formulated as per BIS specifications (1992) were used as duck starter and finisher rations. Ducklings in T: were fed with control ration, T2 control + 0.025 per cent probiotic and T3 control + 0.05 per cent probiotic. Similar managemental practices were followed for all treatments. The 0.05 per cent probiotic supplemented group recorded a significantly higher body weight from second fortnight and followed a similar pattern till the end of the experiment. The fortnightly body weight gains were significantly higher (P<0.05) in 0.05 per cent probiotic supplemented group during the second and fourth fortnights, while the cumulative body weight gain showed a significantly higher (P<O.OI) value in T3 upto six and eight weeks period. The weekly feed consumption was statistically significant (P<O.Ol) and . was higher in 0.05 per cent probiotic supplemented group during third, fourth and C< fifth weeks. The cumulative feed consumption upto six and eight weeks also showed similar trend. The cumulative feed conversion ratio was statistically significant (P<O.O 1) between treatments and superior value was observed in 0.05 per cent supplemented group upto six and eight weeks of age. The serum cholesterol level was not affected by probiotic supplementation. The serum protein level was significantly higher (P<O.OI) in 0.05 per cent probiotic supplemented group. The processing yields were not significantly influenced by probiotics. Livability percentage between treatments was not affected by probiotics. The total feed cost per kg body weight was lower in the 0.05 per cent probiotic supplemented group upto six and eight weeks of age.